Implementation of Effective Sports Human Resource Management Policies in Improving the Performance of Sports Organizations in the Society 5.0 Era - Kodrad Budiyono; Pipit Fitria Yulianto; Teguh Santosa; Helvi Ayu Setyorini; Firdawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Current advances have created very tight competition among Central Java Petanque sports organizations, encouraging the need for extraordinary performance to support national sporting achievements. The change from the previous era to the Society 5.0 Era reflects significant evolution in the industrial revolution, technological progress and social change. In the Era of Society 5.0, the role of the Central Java Petanque sports organization is increasingly important in responding to the dynamics of social and technological change. Human resource management in the Central Java Petanque sports organization faces various challenges, such as the diversity of team members involving differences in culture, language and work styles. Therefore, implementing human resource management policies that focus on sports is very important to compete at the global level, improve sports performance, and support the achievement of national goals in Indonesia's sports achievements. This research uses descriptive qualitative methods. The research results show that its application will face dynamics and challenges regarding limited sports human resources, cultural and value differences, and dynamic flexibility. Therefore, alternative solutions are needed to deal with various problems, such as automation in increasing awareness about the value of various crocodiles, automation that leads to digitalization, as well as developing programs for the involvement of all human resources in sports